2006
DOI: 10.4049/jimmunol.177.12.8466
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Differentiation of CD8 T Cells That Recognize Dominant and Cryptic Antigens

Abstract: Restriction of T cell responses to a few epitopes (immunodominance) is a central feature of immune responses. We analyzed the entire transcriptome of effector CD8 T cells specific for a dominant (H7a) and a cryptic (HY) mouse Ag and performed a longitudinal analysis of selected T cell differentiation markers. We found that Ag specificity had a relatively modest influence on the repertoire of genes that are transcriptionally modulated by the CD8 T cell differentiation program. Although the differentiation progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…57 Features having a fold change greater than 1.5 or smaller than À 1.5 and a P-value smaller than 0.05 were considered as significantly regulated based on previous studies using primary T cells. 9,58 Heat maps and hierarchal clustering were done using the MEV (MultiExperiment Viewer) package. 59 The Panther tool (www.pantherdb.org) was used to categorize gene transcripts according to molecular function and biological process (Gene Ontology analysis).…”
Section: Expression Microarray Data Analysismentioning
confidence: 99%
“…57 Features having a fold change greater than 1.5 or smaller than À 1.5 and a P-value smaller than 0.05 were considered as significantly regulated based on previous studies using primary T cells. 9,58 Heat maps and hierarchal clustering were done using the MEV (MultiExperiment Viewer) package. 59 The Panther tool (www.pantherdb.org) was used to categorize gene transcripts according to molecular function and biological process (Gene Ontology analysis).…”
Section: Expression Microarray Data Analysismentioning
confidence: 99%
“…The 1B11 monoclonal antibody recognizes an isoform of CD43 whose expression is induced on activated CD8 and CD4 T cells and correlates with effector function. 23,24 As for Ifngr2 transcripts modulation, discrepancies between IFN-␥RKO and wt hosts were found on day 4 but not day 8 ( Figure 3D). Effector T cells must up-regulate specific integrins to infiltrate nonlymphoid tissues.…”
Section: High Ifn-␥ Exposure and Rapid T-cell Activation In Ifn-␥rko mentioning
confidence: 82%
“…Although antibody-based vaccines are protective, they usually are serotype specific. A recent study demonstrated that, utilizing regimens favoring T cell response, it was possible to protect in a mouse-adapted influenza model against homosubtypic and heterosubtypic influenza, as the T cell response generated target conserved epitopes among those strains [83,84]. …”
Section: Immunology Of Npsmentioning
confidence: 99%